Metode Istinbath Ahkam Dalam Menyelesaikan Masalah Kontemporer: Studi Kasus Tentang Fatwa dan Ijtihad - Mufadhol, Allam Tri; Nuraeni, Neni (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Istinbath ahkam is the process of deriving Islamic law from the Qur'an and Sunnah through ijtihadi reasoning, taking into account social context and maqashid sharia. In the contemporary era, ijtihad is a key mechanism in responding to changing times and new issues not explicitly addressed in classical sources. Fatwas resulting from collective ijtihad serve as important guidelines for Muslims facing social, technological, and economic dynamics. Istinbath methods such as qiyas, istihsan, maslahah mursalah, and sadd al-dzari'ah are employed to resolve contemporary issues with an inclusive and contextual maqashid approach. Case studies of contemporary fatwas from MUI and international bodies demonstrate the adaptability of Islamic law to digital financial technology, bioethics, and socio-political and environmental issues. Thus, Islamic legal istinbath remains relevant and responsive in safeguarding the welfare of the Muslim community amid modern advancements.